More Kentucky Bourbon Cocktails - Perrine, Joy; Reigler, Susan (Book collections on Project MUSE., 2016)
Ninety-five percent of the world's bourbon whiskey is produced in Kentucky, and the drink is as distinctive to the state as Thoroughbred horses and Bluegrass music. As America's native spirit enjoys booming popularity worldwide, award-winning bartender Joy Perrine and celebrated restaurant critic and drinks writer Susan Reigler return to offer new recipes that will delight both the cocktail novice and the seasoned connoisseur. Following up on their best-selling The Kentucky Bourbon Cocktail Book, the duo returns with more reasons to appreciate bourbon whiskey. This mouthwatering volume features more than fifty delicious new concoctions -- including variations on classics such as the Old Fashioned and the Manhattan -- and even adds a splash of Kentucky flavor to mojitos, sangria, lemonade, and coffee. It also serves up recipes from leading bartenders, prizewinning drinks from cocktail competitions, and a bourbon-inspired buffet featuring edibles that will be a feast for aficionados. The useful bourbon glossary and bibliography will appeal to professional or at-home bartenders eager to experiment, invent, and savor their own recipes.